Long-term treatment of chronic plaque psoriasis with biological drugs can control platelet activation: targeting the bridge between inflammation and atherothrombosis - Kwiek, Bartłomiej; Narbutt, Joanna; Sysa-Jędrzejowska, Anna; Langner, Andrzej; Lesiak, Aleksandra (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Platelet activation is elevated in moderate to severe psoriasis, and the reduction in platelet activation during short-term treatment has already been demonstrated. Soluble P-selectin is a well-established marker of platelet activation. Aim : To show whether the long-term treatment of psoriasis with biological drugs can reduce elevated platelet activation. Material and methods : An observational study of 27 patients with chronic plaque psoriasis, treated with infliximab, adalimumab, etanercept, or ustekinumab for up to 12 months was conducted. Psoriasis area and severity index (PASI), serum P-selectin and interleukin (IL)-6 were monitored throughout the treatment. Results : There was no significant correlation between PASI and platelet activation in our patients. After 3 months of treatment, a significant reduction in PASI and IL-6 was found, while P-selectin was not significantly reduced. When a cohort of patients who had shown elevated P-selectin prior to the treatment was evaluated, a significant reduction in P-selectin was observed in all 8 patients following 3 months; a reduction that was sustained after 6 and 12 months of therapy. Conclusions : We conclude that PASI is not a good predictor of platelet activity in patients with PASI near to 10. Biological drugs reduce platelet activation in patients who have increased platelet activation prior to treatment, and this effect is stable during chronic therapy.